Brief reflections on the canon 1676 of the Code of Canon Law of 1983 - Garín Urionabarrenechea, Pedro (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Before he accepts a case of nullity, the judge must try to persuade the spouses that they should validate their marriage and resume their conjugal life. The reflection studies the context, the meaning and the purpose of this canon, comparing it with the previous and later legislation to reach a reasonable explanation of its possible application.
Keywords: marriage; judge; court; validation; institution; charity; truth